IMPACT OF OBESITY ON DEPRESSION AMONG YOUNGSTERS OF MUZAFFARPUR DISTRICT OF BIHAR - Kiran, Sweta; Kumar, Krishna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rising prevalence of adolescent obesity and its psychological ramifications have become a pressing public health concern globally, with particular urgency in rural regions of India such as Muzaffarpur, Bihar. This study investigates the relationship between obesity and depression among adolescents, drawing on existing literature and empirical evidence. It highlights how social stigma, body image dissatisfaction, peer bullying, and socio-economic disparities contribute to depressive symptoms in obese adolescents. Findings from various Indian studies reveal that obesity not only leads to physical health challenges but also increases vulnerability to mental health disorders, especially depression. Girls and low-income adolescents are particularly at risk due to compounded societal pressures. The paper emphasizes the need for integrated interventions that address both physical and mental health, incorporating school-based programs, family support systems, and public awareness campaigns. Addressing these dual burdens is essential for improving the overall well-being of adolescents in under-resourced rural settings like Muzaffarpur.